2010
DOI: 10.1556/amicr.57.2010.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Induced expression of lectin-like oxidized ldl receptor-1 in vascular smooth muscle cells followingChlamydia pneumoniaeinfection and its down-regulation by fluvastatin

Abstract: Microorganisms such as Chlamydia pneumoniae have been shown to infect vascular cells and are believed to contribute to vascular inflammation and atherosclerotic plaque development. Plasma levels of oxidized low density lipoprotein (oxLDL) have received considerable attention as potential predictors of prognosis in atherosclerotic diseases. Lectin-like oxidized LDL receptor-1 (LOX-1) is one of the major receptors for oxidized LDL. It was investigated whether C. pneumoniae infection can stimulate expression of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…C. pneumoniae also has a role in lipid accumulation in the vessel wall by upregulating lecithin-like oxidized LDL receptors (LOX-1) in both endothelial and vascular smooth muscle cells. [4344] In the same period, four studies[4548] did not find convincing evidence of presence of Chlamydophila genome in the atheromatous tissue, and argued in favor of alternative mechanisms. However, it is likely that C. pneumoniae infection may only be providing an initial trigger and is transient rather than persistent.…”
Section: Resultsmentioning
confidence: 99%
“…C. pneumoniae also has a role in lipid accumulation in the vessel wall by upregulating lecithin-like oxidized LDL receptors (LOX-1) in both endothelial and vascular smooth muscle cells. [4344] In the same period, four studies[4548] did not find convincing evidence of presence of Chlamydophila genome in the atheromatous tissue, and argued in favor of alternative mechanisms. However, it is likely that C. pneumoniae infection may only be providing an initial trigger and is transient rather than persistent.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that C. pneumoniae induces macrophage foam cell formation by the native LDL receptor in the presence of LDL [31]. In 2010 Prochnau et al presented experimental evidence that C. pneumoniae induces also the expression of the scavenger receptor LOX-1 (oxidized LDL receptor-1) in vascular smooth muscle cells [64]. Lin et al showed that GroEL1, a heat shock protein 60 of C. pneumoniae, induces LOX-1 expression in endothelial cells and enhances atherogenesis in hypercholesterolemic rabbits [65].…”
Section: Lipid Droplet Formation In Chlamydia Infectionmentioning
confidence: 95%
“…Such infection induces expression of LOX‐1 in VSMCs. Treatment with fluvastatin, an HMG‐CoA‐reductase inhibitor, decreases LOX‐1 expression . The upregulation of LOX‐1 by such infections and a reduction by fluvastatin provides clue of lipid accumulation in atherosclerotic lesions in microbial infections.…”
Section: Cytotopographical Variancementioning
confidence: 99%